A eficiência técnica do gasto público em educação, saúde e segurança pública - uma análise empírica para os Estados do Ceará, Bahia, Rio Grande do Norte, Piauí, Pernambuco e Paraíba no período de 2007 a 2010 - Carneiro, Kécia Maria Mendes (2017)
The proper use of the public resources available to the states should generate improvements in the quality of life of the population, with the public manager being committed to allocate them efficiently. In this context, this study analyzes the technical efficiency of public spending in the areas of education, health and public safety in the states of Ceará, Bahia, Rio Grande do Norte, Piauí, Pernambuco and Paraíba in the period between 2007 and 2010, highlighting which ones resources invested in these areas. The Stochastic Frontier method was used to obtain the technical efficiency scores of the states, a metric used to compare states in the studied areas. As a result, the state of Ceará was more efficient in spending on education, in the rates of approvals by grade - elementary and high school, alternating between the first positions with Piauí and Pernambuco. The states of Paraíba, Bahia and Rio Grande do Norte occupied the last positions. In the area of health, the highlight was for the state of Bahia and the results with less technical efficiency went to Ceará, Piauí and Pernambuco. The states of Piauí and Paraíba had the highest levels of technical efficiency in the area of Public Safety, while Pernambuco ranked first in inefficiency in the ranking of almost all the models analyzed in this area.